PENGARUH MOTIVASI, KEDISPLINAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ASURANSI ASEI INDONESIA CABANG MEDAN - Buulolo, Rinida; Buulolo, Abadi; Tarigan, Jenni; Sinaga, Dearma (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2023)
This research intends to try the influence of motivation, work discipline and work environment on employee performance at PT. Asuransi Asei Indonesia Medan Branch. In this research, there is a conclusion that the problem is whether motivation, work discipline and work environment have a significant effect on the ability of employees at PT. Ace?. Therefore this research was attempted to identify and analyze the effects. Encouragement, Activity Discipline and Activity Areas to the Ability of Employees at PT. Asuransi Asei Indonesia Medan Branch. In this research using quantitative research procedures. The population in this research is all employees of the Asei Indonesia insurance industry, agents in the research illustration area, totaling 71 people. The information analysis method used is descriptive analysis of respondents, descriptive analysis of variables, classical assumption experiments, multiple linear regression analysis and assumption experiments (t experiments, F experiments and determinant coefficient experiments). The results of the research processed with the SPSS type 23 program, based on the t experiment proved that motivation, activity discipline and the activity environment have a positive and jointly important effect on employee abilities, the adjusted R square number is 0.735 or 73.5%, which means Employee ability is influenced by motivation, activity discipline and activity area and more than 26.5% can be explained by other factors that were not examined in this research. compared to the results of the previous research of the Great God Kresna Valiant. 2017 the effect of communication, encouragement, sports environment on the happiness of employees' activities in the Denpasar city area proves that there is a positive and important effect on employee activity satisfaction. It can be concluded that the results of this research are in line with the results of previous research by AA Besar Oka Pramadita 2015